Mapping of the spatial distribution of silver nanoparticles in root tissues of Vicia faba by laser-induced breakdown spectroscopy (LIBS) - Krajcarová, L; Novotný, K; Kummerová, M; Dubová, J; Gloser, V; Kaiser, J (Talanta, 2017)
The manuscript presents a procedure for optimal sample preparation and the mapping of the spatial distribution of metal ions and nanoparticles in plant roots using laser-induced breakdown spectroscopy (LIBS) in a double-pulse configuration (DP LIBS) in orthogonal reheating mode. Two Nd:YAG lasers were used; the first one was an ablation laser (UP-266 MACRO, New Wave, USA) with a wavelength of 266nm, and the second one (Brilliant, Quantel, France), with a fundamental wavelength of 1064nm, was used to reheat the microplasma. Seedlings of Vicia faba were cultivated for 7 days in CuSO4 or AgNO3 solutions with a concentration of 10µmoll-1 or in a solution of silver nanoparticles (AgNPs) with a concentration of 10µmoll-1 of total Ag, and in distilled water as a control. The total contents of the examined metals in the roots after sample mineralization as well as changes in the concentrations of the metals in the cultivation solutions were monitored by ICP-OES. Root samples embedded in the TissueTek medium and cut into 40µm thick cross sections using the Cryo-Cut Microtome proved to be best suited for an accurate LIBS analysis with a 50µm spatial resolution. 2D raster maps of elemental distribution were created for the emission lines of Cu(I) at 324.754nm and Ag(I) at 328.068nm. The limits of detection of DP LIBS for the root cross sections were estimated to be 4pg for Cu, 18pg for Ag, and 3pg for AgNPs. The results of Ag spatial distribution mapping indicated that unlike Ag+ ions, AgNPs do not penetrate into the inner tissues of Vicia faba roots but stay in their outermost layers. The content of Ag in roots cultivated in the AgNP solution was one order of magnitude lower compared to roots cultivated in the metal ion solutions. The significantly smaller concentration of Ag in root tissues cultivated in the AgNP solution also supports the conclusion that the absorption and uptake of AgNPs by roots of Vicia faba is very slow. LIBS mapping of root sections represents a fast analytical method with sufficient precision and spatial resolution that can provide very important information for researchers, particularly in the fields of plant science and ecotoxicology.
Keywords: Silver; Copper; kovové nanočástice; Vicia faba; spektrální analýza; Lasers; Plant Roots; kořeny rostlin; Metal Nanoparticles; Spectrum Analysis; stříbro; lasery; měď